A Case Study of Zoonotic Chlamydia abortus Infection: Diagnostic Challenges From Clinical and Microbiological Perspectives. (12th October 2022) - Burgener, Anne-Valérie; Seth-Smith, Helena M B; Kern-Baumann, Sina; Durovic, Ana; Blaich, Anette; Menter, Thomas; Bruder, Elisabeth; Roloff, Tim; Martinez, Aurélien; Borel, Nicole; Albini, Sarah; Hösli, Irene; et al.
Abstract: Chlamydia abortus is the most common causative agent of abortion in small ruminants, but it is poorly recognized as a human pathogen. In most published case studies, diagnosis remained difficult and often resulted in delayed initiation of therapy. In this case study of severe C abortus infection in a pregnant farmer from Switzerland, we highlight the clinical and microbiological diagnostic challenges and provide evidence of a zoonotic epidemiological link.